Planteamientos sobre el cumplimiento del marco fiscal de mediano plazo: una aproximación conceptual en Boyac (2018)
This article presents the result of an analysis on the measurement of compliance with the medium-term fiscal framework (MFMP) in the department of Boyacá, and has as its starting point, a review of the literature on the history and evolution of the concept of decentralization established by some authors from the seventeenth century until the epoch of neo - institutionalism and the approach both political, economic and political - administrative approach.Next, a brief review of the fiscal decentralization process in Colombia will be made, with reference to fiscal federalism - understood as the degree to which local tax decisions are decentralized; and finally, the effects of the structural reforms implemented in Colombia concerning fiscal decentralization and implications for fiscal responsibility and transparency in territorial entities; Finally, the methodology to be applied is presented, by means of which a descriptive analytical study is made to arrive at an explanatory study, in order to know how this form of organization has evolved in Colombia and its incidence in the department of Boyacá , focusing the study on compliance with the MFMP as the main tool of public finance planning.